2017
DOI: 10.1177/0146167217711936
|View full text |Cite
|
Sign up to set email alerts
|

Who Gets Social Support, Who Gives It, and How It’s Related to Recipient’s Mood

Abstract: We sought to identify personal characteristics associated with receiving and perceiving social support, and characteristics of support providers who give the most support and are perceived as the most available. In samples of students ( n = 755) and community adults ( n = 430), we found that people who were younger, female, more extraverted, more conscientious, and more open received and perceived more support. Female providers and romantic partners were associated with more support whereas coworkers were asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 127 publications
1
22
0
Order By: Relevance
“…An individual level variable that may explain some differences in the dynamics and patterns of well-being is personality-not explored in this study, but shown in previous research to be linked to well-being facets (Ryff 2014;Schotanus-Dijkstra et al 2016;Williamson and O'Hara 2017). Hentschel et al (2017) found that personality plays a role in well-being, and together with life events explained 30% of well-being variance.…”
Section: Discussionmentioning
confidence: 76%
“…An individual level variable that may explain some differences in the dynamics and patterns of well-being is personality-not explored in this study, but shown in previous research to be linked to well-being facets (Ryff 2014;Schotanus-Dijkstra et al 2016;Williamson and O'Hara 2017). Hentschel et al (2017) found that personality plays a role in well-being, and together with life events explained 30% of well-being variance.…”
Section: Discussionmentioning
confidence: 76%
“…One key line of research has focused on the component of perceived support availability, which has strong associations with health outcomes (Cohen et al, 2001;Uchino, 2009aUchino, , 2009b. This component involves a person's script for typical supportive interactions (Brunson et al, 2015;Lakey & Cohen, 2000;Pierce et al, 1997) and is typically conceptualized as a unidimensional construct with support availability versus unavailability as opposite poles of a single dimension (Goodenow et al, 1990;Williamson & O'Hara, 2017).…”
Section: Components Of Perceived Supportmentioning
confidence: 99%
“…Among adolescents, higher levels of perceived social support increased overall adjustment, increased adaptive behaviors, and decreased externalizing problems in women, whereas perceived social support increased adaptive behaviors and decreased internalizing problems in men (Rueger et al, 2008). Researchers suggest that outcome differences may be attributed to an increased saliency for social support among women (Bámaca-Colbert et al, 2017; Williamson & O’Hara, 2017).…”
Section: Social Support and Self-esteemmentioning
confidence: 99%
“…For adolescents, teachers, classmates, close friends, and school personnel supported females more (Rueger, Malecki, & Demaray, 2010; Williamson & O’Hara, 2017). Women also reported more social support from close friends and mothers, whereas men reported most of their support from their teachers and fathers (Colarossi & Eccles, 2003; Rueger et al, 2010; Williamson & O’Hara, 2017). As individuals age, parental support decreased and peer support became more important (Larsen et al, 2012).…”
Section: Social Support and Self-esteemmentioning
confidence: 99%